Experience in construction of monolithic layers of road pavement at sub-zero air temperatures - A. A. Lytkin (Вестник СибАДИ, 2022)
Introduction. Increasing the durability of road structures and extending the construction season for the installation of monolithic road pavements are urgent tasks. Non-rigid road pavements are of particular interest. Replacing the bases of granular materials (crushed stone, gravel, etc.) with monolithic ones reduces the material consumption of the road surface by 20-50%, the cost of construction works by up to 45% and increases the service life of roads by 1.5-2 times. The extension of the construction season for the installation of monolithic bases contributes to an increase in the pace of construction, a more rational use of road construction equipment, securing highly qualified specialists at the enterprise and reducing overhead costs. A multi-tonnage waste having independent binding properties is of particular interest, for example, belite sludge of alumina production. The article is devoted to a comprehensive study of the physical mechanical and technological properties of natural belite sludge in order to use it for the making of monolithic layers of road and airfield pavement in winter, without the introduction of antifreeze additives.Materials and methods. The freezing temperature of the belite sludge of minus 2 ° C was determined by the thermoelectric method. Its compactibility in the range of negative temperatures, the ability to restore the destroyed structure after re-compaction, the regularities of cooling of the material during technological operations for the construction of structural layers in winter are studied. The compaction was studied by pressing samples from sludge of optimal humidity, at its temperatures from 20 to minus 10°C. The study of the processes of structure formation of sludge and sludge crushed stone materials consisted in studying the kinetics of hardening of samples stored in climatic chambers that simulate changes in average monthly air temperatures in an annual cycle (from 20°C to minus 20°C) and in natural conditions (outdoors). In parallel, thermographic and electron microscopic studies of neoplasms in the hardening material were performed. To study the regularities of the cooling of the sludge layers, a laboratory experiment was conducted that simulates two-way (top and bottom) freezing of the material in a climatic chamber at temperatures of minus 10, minus 15 and minus 25°C.Results. A complex of unique physical chemical and technological properties of natural belite sludge has been identified, which consist in maintaining the initial density and activity after freezing, the ability of sludge and sludge crushed stone materials to harden at negative temperatures, a reduced freezing temperature of minus 2°C, good compaction in the range of negative temperatures (up to minus 6°C). The temperature and technological parameters of the sludge preparation for the production of works in winter are investigated. The regularities of sludge cooling in the technological process for the construction of structural layers in winter are studied. A technology has been developed for the making of monolithic layers of the road pavement made of belite sludge and crushed stone materials at negative air temperatures up to minus 20°C. The practical experience of the belite sludge use in the construction of roads in 2-4 road-climatic zones is summarized.